The Power Trip - Collins, Jackie (London Simon & Schuster, 2012)
A Russian billionaire and his state of the art yacht. His beautiful and sexy supermodel girlfriend. And five dynamic, powerful and famous couples are invited on the maiden voyage. Could this be the trip of a lifetime? Or a trip from hell?
Keywords: Rich people